Tuina for peripherally-induced neuropathic pain: A review of analgesic mechanism - Liu, Zhi-Feng; Wang, Hou-Rong; Yu, Tian-Yuan; Zhang, Ying-Qi; Jiao, Yi; Wang, Xi-You (Frontiers in Neuroscience, 2022)
Peripherally-induced neuropathic pain (pNP) is a kind of NP that is common, frequent and difficult to treat. Tuina, also known as massage, manual therapy, has been used to treat pain in China for thousands of years. It has been clinically proved to be effective in the treatment of pNP caused by cervical Spondylotic radiculopathy, lumbar disc herniation, etc. However, its analgesic mechanism is still not clear and has been the focus of research. In this review, we summarizes the existing research progress, so as to provide guidance for clinical and basic studies. The analgesic mechanism of tuina is mainly manifested in peripheral and central aspects. At the peripheral level, tuina can inhibit peripheral inflammation and regulate ion channels. At the central level, tuina can inhibit the activation of glial cells, upregulate autophagy in spinal cord, and adjust the brain functional alternations. Overall, tuina plays an analgesic effect by acting on different levels of targets, and it is an effective therapy for the treatment of pNP, it is necessary to continue to study the mechanism of tuina analgesia.